2014
DOI: 10.1186/s13567-014-0085-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous pathological outcomes after experimental pH1N1 influenza infection in ferrets correlate with viral replication and host immune responses in the lung

Abstract: The swine-origin pandemic (p) H1N1 influenza A virus causes mild upper-respiratory tract disease in most human patients. However, some patients developed severe lower-respiratory tract infections with fatal consequences, and the cause of these infections remain unknown. Recently, it has been suggested that different populations have different degrees of susceptibility to pH1N1 strains due to host genetic variations that are associated with inappropriate immune responses against viral genetic characteristics. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 63 publications
(82 reference statements)
2
20
1
Order By: Relevance
“…In contrast to previous studies that reported increased CXCL8 expression in the lungs of H1N1 (A/CastillaLaMancha/RR5661/2009 and A/CastillaLaMancha/RR5911/ 2009)-infected ferrets, H1N1 (A/PR/8/34)-infected lung epithelial cells (1,47), and BAL of macaques infected with CA04 (19), the levels of this chemokine in the BAL did not change in our current study. This may be due to differences in tissues (lung vs. BAL) or severity of disease (the macaques in our study controlled viral replication more quickly than previously reported for CA04).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies that reported increased CXCL8 expression in the lungs of H1N1 (A/CastillaLaMancha/RR5661/2009 and A/CastillaLaMancha/RR5911/ 2009)-infected ferrets, H1N1 (A/PR/8/34)-infected lung epithelial cells (1,47), and BAL of macaques infected with CA04 (19), the levels of this chemokine in the BAL did not change in our current study. This may be due to differences in tissues (lung vs. BAL) or severity of disease (the macaques in our study controlled viral replication more quickly than previously reported for CA04).…”
Section: Discussioncontrasting
confidence: 99%
“…Alveolar areas were also shown to contribute to the influx of inflammatory cells by the up-regulation of IFNα, IL-6 and IL-8, at 12 hpi, and CCL3 and IFNγ, at 24 hpi. The up-regulation of IL-8, IFNγ and CCL3 has been related to lung recruitment of neutrophils, NK and T cells and the development of severe influenza infection [8, 14, 19, 29]. In addition, TNFα and IL-6 up-regulation mediate phagocytic inflammatory infiltration and the apoptosis of infected cells [10, 30], which has also been associated with severe lung lesions after IAV [7, 11, 31].…”
Section: Discussionmentioning
confidence: 99%
“…RIG-I is activated by the detection of viral RNA in replication and its activation has been associated with protective and enhanced T cell responses against infection and the induction of IFN responses [8, 36]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations